Public Opinion on Immigration in Europe: Preference versus Salience - Timothy J. Hatton (Institute of Labor Economics (IZA), 2017)
There is growing interest among economists in public opinion towards immigration, something that is often seen as the foundation for restrictive immigration policies. Existing studies have focused on the responses to survey questions on whether the individual would prefer more or less immigration but not on his or her assessment of its importance as a policy issue. Here I distinguish between preference and salience. Analysis of data from the European Social Survey and Eurobarometer indicates that these are associated with different individual-level characteristics. At the national level these two dimensions of public opinion move differently over time and in response to different macro-level variables. The results suggest that both dimensions need to be taken into account when assessing the overall climate of public opinion towards immigration. Finally, there is some evidence that both preference and salience are important influences on immigration policy.
Keywords: D72; F22; J61; 330; attitudes to immigration; salience; public opinion